2011
DOI: 10.1177/0892705711415740
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polar interactions on the structure and rheology of EVA/Montmorillonite nanocomposites

Abstract: In this study we utilized X-ray diffraction, transmission electron microscopy (TEM) and various types of simple shear flow experiments to investigate the effect of the polarpolar interaction between ethylene-vinyl acetate co-polymers (EVA) and organo-silicates on the nanoscale structures and rheological properties of their melt blends.The WAXS intensities and TEM micrographs demonstrate that the exfoliation and the intercalation of nanoclays respectively prevail in EVA/Cloisite 30B nanocomposites and EVA/Clois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…In other words, this would reduce the compatibility of NMMT and ATH fillers in LE matrix with noticeable decrement in the tensile strength. This observation was also found to be different from previous studies of Merinska et al 16 and Su et al 17 They reported that the addition of NMMT in polymer could provide reinforcement effect to the polymer matrix by modifying the interfacial adhesion between the NMMT particles and polymer matrix. However, the tensile strengths of 80, 120 and 150 phr ATH added LE blends were observed to gradually increase with the increasing of NMMT loading levels.…”
Section: Mechanical Properties and Surface Morphologiescontrasting
confidence: 94%
“…In other words, this would reduce the compatibility of NMMT and ATH fillers in LE matrix with noticeable decrement in the tensile strength. This observation was also found to be different from previous studies of Merinska et al 16 and Su et al 17 They reported that the addition of NMMT in polymer could provide reinforcement effect to the polymer matrix by modifying the interfacial adhesion between the NMMT particles and polymer matrix. However, the tensile strengths of 80, 120 and 150 phr ATH added LE blends were observed to gradually increase with the increasing of NMMT loading levels.…”
Section: Mechanical Properties and Surface Morphologiescontrasting
confidence: 94%
“…From the nanocomposites point of view, these two ethylene- and polar-monomer-based copolymers (EVA and EVOH) have a much higher number of polar functional groups than the typically used polyolefin-MAH-grafted copolymers, making them good candidates to produce exfoliated MMT structures. In the case of the binary EVA/MMT nanocomposites, mainly exfoliated structures with intercalated tactoids have been reported [ 25 , 26 , 27 , 28 ], whereas for the binary EVOH/MMT nancomposites, intercalated structures with small exfoliation are seen [ 29 , 30 , 31 , 32 ]. In this way, according to MMT exfoliation, better barrier properties are expected for the PP/EVA/MMT nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…4 In many cases, addition of only a small amount of nano-clay to the polymer matrix is sufficient to make noticeable improvements in mechanical properties, thermal stability, heat distortion temperature, barrier performance, and flame retardance. 5 12 There are three main methods to prepare polymer–clay NCs, that is, solution methods, melt-processing methods, and in situ polymerization. 13 Most of the published works have focused on organically modified smectite clays, in particular montmorillonites, as fillers of polymeric composites.…”
Section: Introductionmentioning
confidence: 99%